A Neo-Kantian Account of Perception. (15th May 2018) - Stevenson, Leslie
Abstract: I suggest a reconstruction of Kant's theory of perception – in particular his notions of intuition, concept, sensible impression, sensation, synthesis and combination – informed by the progress of philosophy and human and animal psychology since his time. I take from Burge the distinction between unconceptualized perception of objects (found in animals, infants, and to some extent in adult humans) and our conceptualized, judgmental perceptual experience. Kant concentrated on the latter, but he can be seen to leave room for the former, especially if we make clearer distinctions than he did between sensible impression and sensation, and between synthesis and combination.